Emergency Medical Services: a resource for victims of domestic violence?. Issue 7 (28th June 2010) - Mason, R; Schwartz, B; Burgess, R; Irwin, E
Abstract : Background: Domestic violence (DV), also known as intimate partner violence (IPV), is one of the leading causes of serious injury among women of childbearing age. As first responders on the scene during DV calls where personal injuries have occurred, Emergency Medical Services (EMS) could routinely identify, report and assist victims of violence. Yet, little is known of the prevalence of DV calls in EMS practice, Emergency Medical Technicians' (EMT) knowledge and comfort in responding to such calls, or how they care for victims. Method: The objectives of this study were to assess EMTs' knowledge of and experience with providing care to victims of DV in the province of Ontario, Canada. Data were gathered through an online, short-answer survey. Survey data were analysed using basic frequency displays, and descriptive statistics are reported. Results: Almost 500 EMTs participated in this study, the vast majority of whom (90%) attended at least one DV call in the preceding year, with 65% attending between 10 and 20 DV calls. The majority of respondents (84.5%) wished for more education and training on the issue. Conclusion: EMTs have frequent contact with victims of DV yet have received little education about the issue. The majority of those surveyed would like specific education and training on DV.